The Impact of Computer-based Test and Students’ Ability in Computer Self - Efficacy on Mathematics Learning Outcomes - H., Nurhikmah; Febriati, Farida; Ervianti, Ervianti; Sujarwo, Sujarwo (Journal of Education Technology, 2021)
The current era of digitalization has big impact on education, the use of technology and information is not only for learning but as an evaluation tool. This development raises problems that require the completion of high-level thinking, therefore students need to prepare the ability to think and be able to develop skills. This study aims to measure the self-efficacy of computer skills on student learning outcomes and interactions in mathematics subjects. This research method used quantitative approach in Quasi Experiment Design. Total sample were 64 students. CBT was used in evaluating mathematics subjects and using a questionnaire to determine the level of self-efficacy of computer abilities towards students learning outcomes. Analysis of research data was carried out using ANOVA, to test the hypothesis using two-way ANOVA (two-way ANOVA) using the SPSS version 25.0 for windows software program. The results showed that there was CBT of mathematics subjects towards student learning outcomes with a mean score of 85 in and a mean score of 80 with a criterion of 3.03, having impact and the criteria value 2.78. The interaction between computer-based tests with self-efficacy computer capabilities had the most correlation with a positive relationship. It can be stated that there is an impact of computer-based tests and self-efficacy of computer ability and has an interaction between CBT and self-efficacy on learning outcomes.